2020
DOI: 10.1021/acs.jpcc.0c04199
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Exploration of the Charge Dynamics in Surface-Passivated ZnO Nanowires

Abstract: One-dimension ZnO nanowires (NWs) are widely used in many optoelectronic devices owing to their high optical transparency and excellent electron-transporting property. Unfortunately, there are various shallow-level and deep-level states in ZnO NWs, which usually act as the charge recombination centers of the devices. Surface passivation is an effective way to reduce deep-level states in ZnO NWs. However, how the surface passivation affects the charge dynamic process in ZnO NWs is still unclear. Herein, we carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…While the peaks ≈410 and 550 nm can be attributed to the emission from the shallow defect and deep defect, respectively. [ 57 ] After incorporating the diradical molecules, the deep‐defect emission of ZnO NP is substantially suppressed and the intrinsic emission increases accordingly. The area ratio of the two emission peaks ≈380 and 550 nm increases from 0.012 of the neat ZnO NP film to 0.017 of ZnO + Flu‐C8, 0.022 of ZnO + Flu‐EH and 0.081 of ZnO + TPAOMe‐C8.…”
Section: Resultsmentioning
confidence: 99%
“…While the peaks ≈410 and 550 nm can be attributed to the emission from the shallow defect and deep defect, respectively. [ 57 ] After incorporating the diradical molecules, the deep‐defect emission of ZnO NP is substantially suppressed and the intrinsic emission increases accordingly. The area ratio of the two emission peaks ≈380 and 550 nm increases from 0.012 of the neat ZnO NP film to 0.017 of ZnO + Flu‐C8, 0.022 of ZnO + Flu‐EH and 0.081 of ZnO + TPAOMe‐C8.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that shallow defect states in ZnO can not only improve the electron mobility of ZnO, but also act as an additional path for electron injection from the QD layer to the NWs in some cases [ 103 ]. Instead, the deep-level trapping states are the critical target of defect passivation because they mainly serve as the recombination centers of photocarriers [ 104 ]. Generally, green and yellow emissions in the PL spectra of ZnO are assigned to deep-level defects (red emissions are associated with either surface oxygen or surface OH groups), while violet and blue emissions are related to shallow defects [ 101 ].…”
Section: Optimization Strategies Of Ibhj Qdscs Based On Zno Nwsmentioning
confidence: 99%
“…Parallel to the class of passivation strategies for post-annealing and surface treatment, depositing organic/inorganic coatings to passivate the surface of ZnO NWs were also investigated [ 91 , 109 ]. Zhang et al [ 104 ] clarified in detail the influence of surface passivation on the charge dynamic process in ZnO NWs by employing time-resolved photoluminescence (TRPL) and transient absorption (TA) spectroscopy techniques, as shown in Figure 9 b. After passivation, the PL intensity of the deep-level defects related emission clearly decreased and the time constants of the two recombination pathways (R1 pathway, in which free electrons are trapped by defect states, and the R2 pathway, in which free electrons are recombined with the holes of PbS QDs) increased, which confirmed the positive effect of the surface passivation layer.…”
Section: Optimization Strategies Of Ibhj Qdscs Based On Zno Nwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though using ZnO NWs as ETL alleviates the problem of limited carrier diffusion length, the accompanying increased contact interface and inherent defects also impede higher PCE for the device. , To overcome this, surface treatment on ZnO NWs with organic or inorganic materials is extensively employed to passivate the surface defects. Chen et al .…”
Section: Introductionmentioning
confidence: 99%